Penerapan Firebase Realtime Database Pada Aplikasi Media Informasi dan Pendaftaran Training IT Berbasis Android - Angga Arindra Shonta; Laily Nur Hamidah; Muhamad Hasan; Melany Mustika Dewi; Yuli Astuti; Irma Rofni Wulandari (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Jogja IT Training Center (JITC) is a business entity that provides training in the field of information technology. JITC provides various kinds of related training. As a business entity engaged in the service sector, the dissemination of information is very important. Currently, JITC uses social media Facebook and Instagram to convey information to the public, but currently, it is not managed properly due to limited resources so the delivery of information and student registration is hampered. The student registration method is done manually and has to come to the office, so the number of students has decreased and resulting in a decrease in income. The conventional registrar data collection has many shortcomings, namely the data is not well documented, resulting in data loss and the search process takes a lot of time. Based on the existing problems, an android-based information and registration media application was built, this mobile application added the Firebase Realtime Database as a data storage platform for information and registrant data so that the training data can be accessed online and in real-time which can be integrated into one service. Firebase Realtime Database has many features and is accessed for free and has a fairly large data storage limit. The result of this research is an android-based application for information providers and registration services for new students.